Spiking and Membrane Properties of Rat Olfactory Bulb Dopamine Neurons - Korshunov, Kirill S.; Blakemore, Laura J.; Bertram, Richard; Trombley, Paul Q. (Frontiers in Cellular Neuroscience, 2020)
The mammalian olfactory bulb (OB) has a vast population of dopamine (DA) neurons, whose function is to increase odor discrimination through mostly inhibitory synaptic mechanisms. However, it is not well understood whether there is more than one neuronal type of OB DA neuron, how these neurons respond to different stimuli, and the ionic mechanisms behind those responses. In this study, we used a transgenic rat line (hTH-GFP) to identify fluorescent OB DA neurons for recording via whole-cell electrophysiology. These neurons were grouped based on their localization in the glomerular layer (“Top” vs. “Bottom”) with these largest and smallest neurons grouped by neuronal area (“Large” vs. “Small,” in μm2). We found that some membrane properties could be distinguished based on a neuron’s area, but not by its glomerular localization. All OB DA neurons produced a single action potential when receiving a sufficiently depolarizing stimulus, while some could also spike multiple times when receiving weaker stimuli, an activity that was more likely in Large than Small neurons. This single spiking activity is likely driven by the Na+ current, which showed a sensitivity to inactivation by depolarization and a relatively long time constant for the removal of inactivation. These recordings showed that Small neurons were more sensitive to inactivation of Na+ current at membrane potentials of -70 mV and -60 mV than Large neurons. The hyperpolarization-activated H-current (identified by voltage sags) was more pronounced in Small than Large DA neurons across hyperpolarized membrane potentials. Lastly, to mimic a more physiological stimulus, these neurons received ramp stimuli of various durations and current amplitudes. When stimulated with weaker/shallow ramps, the neurons needed less current to begin and end firing and they produced more action potentials at a slower frequency. These spiking properties were further analyzed between the four groups of neurons, and these analyses support the difference in spiking induced with current step stimuli. Thus, there may be more than one type of OB DA neuron, and these neurons’ activities may support a possible role of being high-pass filters in the OB by allowing the transmission of stronger odor signals while inhibiting weaker ones.